Cognitive Assessment of Grade 6 Students of Slarang 02 Kesugihan Elementary School on the Material of Diseases Attacking the Movement System with the Ana Test Application - Puji Lestari; Subuh Anggoro (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to evaluate the cognitive assessment of grade VI students at Slarang 02 Kesugihan Elementary School on the material of Diseases that Attack the Movement System using the Ana Test application. Cognitive assessment is an important part of the learning process to determine the level of understanding and mastery of students' concepts of the material being taught. The research method used is quantitative descriptive with 20 grade VI students as research subjects. The instrument used was multiple-choice questions that were developed and analyzed through the Ana Test application to obtain information about the validity, reliability, level of difficulty, discriminatory power, and effectiveness of the question distractors. The results of the analysis showed that most of the questions were in the valid and reliable categories, with a moderate level of difficulty and quite good discriminatory power. These findings indicate that the Ana Test application can be used effectively as a tool in analyzing the quality of questions and assessing student learning outcomes, especially in the material of the movement system. This study recommends the use of technology in learning assessment as an effort to improve the quality of learning at the elementary school level.